IoT Monitoring System for Ornamental Fish Water Quality Control: Sistem Pemantauan IoT untuk Pengendalian Kualitas Air Ikan Hias - Muhammad Firhand Setiaky; Shazana Dhiya Ayuni; Dwi Hadidjaja Rasjid Saputra; Syamsudduha Syahrorini (Indonesian Journal of Innovation Studies, 2025)
General Background Ornamental fish cultivation requires consistent environmental control to maintain optimal health and productivity. Specific Background Key parameters such as temperature, total dissolved solids, and water flow significantly determine the success of fish grooming processes. Knowledge Gap Manual monitoring is often inconsistent due to user limitations, leading to suboptimal environmental conditions and reduced fish quality. Aims This study aims to design and implement an Internet of Things-based monitoring system to observe water quality and automate feeding processes in real time. Results The system integrates ESP8266, temperature sensors, TDS sensors, and water flow sensors, transmitting data to a spreadsheet platform. Experimental results show stable temperature at 31°C and TDS at 158 ppm, while water flow varies depending on filter conditions and pump capacity. Novelty The integration of real-time monitoring with automated feeding and filtration analysis provides a practical solution for continuous fish care. Implications This system supports efficient water quality management, reduces manual workload, and enables data-driven decision-making for improving ornamental fish cultivation outcomes. Keywords: IoT Monitoring, Water Quality, Ornamental Fish, ESP8266, Sensor System Key Findings Highlights Real-time sensing ensures stable aquatic conditions across multiple parameters Automated feeding mechanism operates accurately using time-based control Filtration performance can be evaluated through flow rate variation patterns